Associative and Strategic Study Approaches: Their Significant Relationships to Solving Meta Cognitive Problems of Mathematics Majors - Marvin Daguplo (JPAIR Institutional Research Journal)
University students still found difficulties in working successfully mathematical word problems. Some researchers attributed this to students' weak cognitive and abstract thinking. To address such problem, this study aimed to understand student's cognitive approaches in processing mathematics information to determine students' level of cognition and come up with classroom activities that enhance the desired approaches in processing mathematical information which influences learning. A total of thirty-seven students of SLSU – Tomas Oppus were the respondents of this descriptive-correlational study. A standardized Mathematics Information Processing Scale (Cronbach's alpha coefficient=.89) was utilized to gather the data for this study. Statistical analysis revealed that there is no significant difference in the performance of male and female mathematics majors in solving word problems who performed at below average level. The same finding is found between male and female mathematics majors in their approaches in processing mathematics information when solving metacognitive problems, when doing deep-associative study, and when doing strategic study. Correlational analysis revealed that a strong relationship exists between solving metacognitive problems and doing associative and strategic study approaches. This study concludes that students who apply associative and strategic study methods perform well in solving meta-cognitive problems.